IDENTIFIKASI UKURAN TUBUH DAN KUALITAS SEMEN SAPI KUANTAN JANTAN - Yendraliza Yendraliza; Husnul Abadi; Restu Misrianti; Arsyadi Ali; Anwar Effendi (JURNAL ILMIAH PETERNAKAN TERPADU, 2019)
Kuantan cattle is one of the Indonesia's local cattle originating from Riau Province. This research were aimed to determine the average body size and test the fresh semen quality of Kuantan cattle. Measurements of Kuantan cattle body were carried out in 16 adult bulls by observing body length, chest circumference, and shoulder height. Semen quality testing was carried out on four years old bulls with ±150kg weight with the parameters are odor, color, pH, volume, consistency and degrees of viscosity, motility, viability and abnormality. The results showed that the average body size of cattle in Kuantan included body length (cm), chest circumference (cm) and shoulder height (cm) of Kuantan cattle were 88.45 ± 3.92, 119.77 ± 16.18 and 98.94 ± 10.28, while motility, viability, abnormalities were 75.00%, 81.33%, 6.8%. The conclusions of this study were Kuantan cattle body size in small size and the semen feasible to be diluted into frozen semen. Keywords: Body Size, Semen Quality, Kuantan Cattle